2008
DOI: 10.1016/j.neuropsychologia.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The right parietal lobe is critical for visual working memory

Abstract: Neuroimaging evidence suggests that the parietal lobe has an important role in memory retrieval, yet neuropsychology is largely silent on this topic. Recently, we reported that unilateral parietal lobe damage impairs various forms of visual working memory when tested by old/new recognition. Here, we investigate whether parietal lobe working memory deficits are linked to problems at retrieval. We tested two patients with bilateral parietal lobe damage in a series of visual working memory tasks that probed recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 86 publications
7
61
0
2
Order By: Relevance
“…This implies that the right IPC can compensate for a suppression of the left IPC but not vice versa. In line with previous findings, patients with right parietal lesions, often lacking symptoms of hemispatial neglect (Vallar and Perani, 1986), are impaired in visuospatial working memory (Berryhill and Olson, 2008). The opposite effect has recently been demonstrated in a TMS study showing improved performance in a visuospatial working memory task when applying resting motor threshold TMS to the right PPC during the delay period (Yamanaka et al, 2010).…”
Section: Working Memory Maintenance (Memory Delay)supporting
confidence: 87%
“…This implies that the right IPC can compensate for a suppression of the left IPC but not vice versa. In line with previous findings, patients with right parietal lesions, often lacking symptoms of hemispatial neglect (Vallar and Perani, 1986), are impaired in visuospatial working memory (Berryhill and Olson, 2008). The opposite effect has recently been demonstrated in a TMS study showing improved performance in a visuospatial working memory task when applying resting motor threshold TMS to the right PPC during the delay period (Yamanaka et al, 2010).…”
Section: Working Memory Maintenance (Memory Delay)supporting
confidence: 87%
“…These fMRI data point toward parietal involvement in WM maintenance, but converging evidence from neuropsychological patients is only partly consistent with this view. We found that patients with bilateral parietal damage were selectively impaired at blocks of WM trials probed by old/new recognition but not recall (Berryhill and Olson, 2008b). Yet, when recall and recognition WM trials were intermingled making the retrieval demands unpredictable these same patient www.frontiersin.org participants could perform normally on recognition WM trials (Berryhill et al, 2011).…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, we expected to find interaction effects between theta and gamma oscillations at parietal and occipital regions. As suggested by several neuroimaging studies (Jonides et al, 1993;D'Esposito et al, 1998;Berryhill and Olson, 2008;van der Ham et al, 2009) visuospatial working memory is lateralized with stronger right hemispheric activation. Thus, it was hypothesized that memory matching-related theta-gamma phase coupling should be stronger at right compared to left posterior recording sites.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 80%
“…Blue lines indicate higher interregional phase coupling for the non-match than match, red lines indicate higher interregional phase synchronization for the match than non-match condition. working memory (Jonides et al, 1993;Berryhill and Olson 2008). Moreover, evidence indicates that there is hemispheric specialization regarding the processing of visual features.…”
Section: Cross-frequency Phase Synchronizationmentioning
confidence: 99%